Manufacture of piping components for nuclear power plants - "Bartecek, R [Vitkovicke Zelezarny Klementa Gottwalda, Ostrava (Czechoslovakia)]" (1983)
Hammer forging of hollow forging ingots, extrusion and elestroslag remelting may be used for the manufacture of large pipes. Technologies have been developed for the manufacture of elbows based on various types of forming. These procedures mainly include the hydraulic pressing of elbows from tubes and the pressing of symmetrical halves of elbows with subsequent welding. The hammer forging of valves, cross pieces, etc., has been replaced by forging and pressing. In order to prevent failures from occurring in the pipes during operation of nuclear power plants, pipes are being made of larger forgings, which reduces the number of welds. This improves the quality of the pipes, reduces production and assembly costs, and is metal-saving.
Keywords: "21 SPECIFIC NUCLEAR REACTORS AND ASSOCIATED PLANTS"; "PIPES"; "PRODUCTION"; "WWER TYPE REACTORS"; "EXTRUSION"; "FORGING"; "PIPE FITTINGS"; "PRESSING"; "PRIMARY COOLANT CIRCUITS"; "WELDING"; "COOLING SYSTEMS"; "ENERGY SYSTEMS"; "ENRICHED URANIUM REACTORS"; "FABRICATION"; "JOINING"; "MATERIALS WORKING"; "PWR TYPE REACTORS"; "REACTOR COMPONENTS"; "REACTOR COOLING SYSTEMS"; "REACTORS"; "THERMAL REACTORS"; "WATER COOLED REACTORS"; "WATER MODERATED REACTORS"; "210200* - Power Reactors, Nonbreeding, Light-Water Moderated, Nonboiling Water Cooled"